Clinico – Histopathological Study of Exudative Epidermitis Caused by S. hyicus in Swine - Baruah, Moloy Sarmah; Phukan, Arabinda; Sharma, Rajib Kr; Dutta, Biswajit; Hazarika, Razibuddin A. (Indian Journal of Hill Farming, 2017)
This study to determine the infection of S. hyicus in swine and its prevalence and associated histopathological alteration in the affected skin. The study was conducted in 349 pigs of different age groups from organized, semi organized and unorganized pig farms of Kamrup district of Assam, of which 34 numbers (9.91 %) were confirmed for exudative epidermitis based on clinical signs, isolation and identification of causative organism and by protein profiling of S. hyicus by detecting 30 kDa virulence indicative protein band through SDS-PAGE. The histopathological examination of affected pig skin showed mild hyperplasia of the stratum corneum, as indicated by the presence of invasion of stratum germinativum by neutrophils, leading to pustule formation; acanthosis and lengthening of the interpapillary pegs. There was abscessation of the hair follicle, also degeneration and ulceration of the stratum germinativum and invasion of the dermis. The epidermal and dermal lesions involving the follicles were also shows neutrophilic invasion and the presence of clusters of bacteria. Highest prevalence of exudative epidermitis (64.70%) were observed in the piglets of age group 1 to 7 days old followed by piglets of age group 8 days to 8 weeks (29.41% ).